SAYAN: COOPERATION MECHANISM IN RURAL MULTI-RELIGIOUS COMMUNITIES - Katon Setyawan; Kusnul Khotimah (Jurnal Partisipatoris, 2021)
Rural communities in Indonesia are still close and strong in implementing cooperation. This research was conducted in Resapombo Village, Blitar Regency with the term cooperation which is popular in the community is Sayan or movement. This research uses a qualitative approach to phenomenological perspective. The research findings show that the multi-religious community still carries out activities in the type of house, in public facilities, and places of worship. These three forms are carried out by interfaith communities. The interfaith community thinks that this is a mechanism that is widely implemented to support harmony among religious believers. Sayan did not see the religious boundaries between one and the other. Nevertheless, some religious leaders do not want the existence of a place of worship. This is considered as an individual view of ordinary people. It's just that other figures disagree with this, there are still figures who argue that the place of worship can still be carried out interfaith.